Research on Image De-fog Algorithm Based on Fusion Homomorphic Filtering and Wavelet Transform - DONG Jing-wei; ZHAO Chun-li; HAI Bo (Journal of Harbin University of Science and Technology)
Aiming at the problem of severe degradation of fog weather image and low contrast, an improved algorithm is proposed . From the point of view of time frequency analysis, the Fourier transform in the homomorphic filtering algorithm is replaced by the fast wavelet transform, and then the wavelet coefficients are processed by the improved filter in the transform domain to achieve the enhanced fog image purpose. The experimental results show that the improved algorithm can effectively correct the fog image illumination, keep the original information of the image is not lost, enhance the contrast of the image, and make the processed image more visible